2012
DOI: 10.1128/aem.06477-11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature, Relative Humidity, Absolute Humidity, and Evaporation Potential on Survival of Airborne Gumboro Vaccine Virus

Abstract: Survival of airborne virus influences the extent of disease transmission via air. How environmental factors affect viral survival is not fully understood. We investigated the survival of a vaccine strain of Gumboro virus which was aerosolized at three temperatures (10°C, 20°C, and 30°C) and two relative humidities (RHs) (40% and 70%). The response of viral survival to four metrics (temperature, RH, absolute humidity [AH], and evaporation potential [EP]) was examined. The results show a biphasic viral survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 49 publications
(47 reference statements)
2
42
1
2
Order By: Relevance
“…The desiccation of the already collected bioaerosols, together with the desiccation of agar media, contributed to decreased microorganism recovery (16). We found no reports on the impact of dehydration on cell membrane integrity; however, the protein coating of airborne Gumboro virus was reported to be damaged at a lower humidity level (59). The data presented in our study clearly show that cell membrane rupture is more substantial with prolonged sampling periods, which was demonstrated by higher I D values for samples exposed to dry air for an extended sampling period than for those without such exposure.…”
Section: Discussioncontrasting
confidence: 40%
“…The desiccation of the already collected bioaerosols, together with the desiccation of agar media, contributed to decreased microorganism recovery (16). We found no reports on the impact of dehydration on cell membrane integrity; however, the protein coating of airborne Gumboro virus was reported to be damaged at a lower humidity level (59). The data presented in our study clearly show that cell membrane rupture is more substantial with prolonged sampling periods, which was demonstrated by higher I D values for samples exposed to dry air for an extended sampling period than for those without such exposure.…”
Section: Discussioncontrasting
confidence: 40%
“…Thus, we recommend that future survival experiments be performed over shorter time periods that allow more confidence for interpolation. Experiments should also include the effect of other potential processes that affect HeV survival, such as desiccation and UV radiation (Zhao et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the infectivity of IBDV can be modulated at higher as well as lower temperatures [41,42]. The effects of humidity and evaporation have been studied extensively on air borne IBDV vaccine strains [43]. In the present study, we are evaluating the effectiveness of the vaccine strains of IBDV at different temperature and pH conditions.…”
mentioning
confidence: 97%